2014
DOI: 10.1002/chem.201402066
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Total Synthesis of Cyclic Lipodepsipeptides as a Premise to Investigate their Self‐Assembly and Biological Activity

Abstract: A rapid and efficient total synthesis is reported for the cyclic lipodepsipeptide pseudodesmin A. This member of the Pseudomonas viscosin group is active against Gram-positive bacteria and features self-assembling properties. A conserved serine residue within the lactone macrocycle is exploited for initial immobilization on 2-chlorotrityl chloride resin through ether formation with the side-chain alcohol. Subsequent elongation proceeds through Fmoc solid-phase peptide synthesis, including automated incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 73 publications
(107 reference statements)
0
60
0
Order By: Relevance
“…These extended reaction times were found to cause considerable epimerization. However, optimized conditions were found resulting in complete conversion to 7 with a limited amount (15%) of epimerization (Figure (A)) . Although these conditions were applied for the synthesis of more than 30 pseudodesmin analogues, comprising both modifications of amino acids (besides the 2nd residue) as well as the lipid moiety (unpublished data), we here observed that the synthesis of 8 turned out to be extremely cumbersome (Figure (B)), when applying identical conditions.…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…These extended reaction times were found to cause considerable epimerization. However, optimized conditions were found resulting in complete conversion to 7 with a limited amount (15%) of epimerization (Figure (A)) . Although these conditions were applied for the synthesis of more than 30 pseudodesmin analogues, comprising both modifications of amino acids (besides the 2nd residue) as well as the lipid moiety (unpublished data), we here observed that the synthesis of 8 turned out to be extremely cumbersome (Figure (B)), when applying identical conditions.…”
Section: Resultsmentioning
confidence: 75%
“…This residue thus appears to be a key residue in determining the properties of the CLP. As part of a larger project aiming to gain more insight in the structure–activity relationship within the viscosin group of CLPs, the earlier developed total synthesis strategy for pseudodesmin A was exploited to carry out a synthetic Ala scan, resulting among others in a so‐called pseudodesmin Q2A analogue . It occurred to us that this synthetic route could be equally expanded towards WLIP, essentially being a pseudodesmin Q2E analogue (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations